1993
DOI: 10.1164/ajrccm/147.4.870
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Voluntary Ventilation: Spirometric Determinants in Chronic Obstructive Pulmonary Disease Patients and Normal Subjects

Abstract: The 12-s maximum voluntary ventilation (MVV) provides an estimate of the ventilatory reserves available to meet the physiologic demands of exercise. Earlier studies established a general relationship between MVV and FEV1. We hypothesized that the resting maximum inspiratory flow rate (MIFR) also serves as a clinically useful predictor of the MVV. A total of 105 subjects, 45 women and 60 men (age 57 +/- 5 yr, mean +/- SD), with expiratory impairment categories of severe (n = 26), moderate (n = 22), mild (n = 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 13 publications
1
32
1
1
Order By: Relevance
“…27 Our data show that FIVC was 94.4% of the FEVC, which is within the range of these suggestions. Additionally, we found that FIF50 was 80.7 AE 17% of PIF, which was lower than suggested for adults.…”
Section: Quality Controlsupporting
confidence: 90%
See 1 more Smart Citation
“…27 Our data show that FIVC was 94.4% of the FEVC, which is within the range of these suggestions. Additionally, we found that FIF50 was 80.7 AE 17% of PIF, which was lower than suggested for adults.…”
Section: Quality Controlsupporting
confidence: 90%
“…Another recommendation is to select the best curve for interpretation from the largest sum of FIVC þ FIF50 þ PIF. 24,26,27 We used FIVC þ PIF only because we did not find any advantage for choosing the sum of three parameters over the sum of two parameters in the young children.…”
Section: Quality Controlmentioning
confidence: 99%
“…It has been shown that maximal minute ventilation measurement is influenced by both inspiratory and expiratory flow rates. 27 Moreover, subjects' motivation and effort can affect the maneuver. 19 ITL is a more specific test to evaluate inspiratory muscle performance.…”
Section: Discussionmentioning
confidence: 99%
“…fixed, variable extrathoracic or variable intrathoracic) because this will markedly influence the ratio of maximal expiratory over inspiratory flows [8]. Therefore, the measured MBC (MBCm) and not MBCc appears to be the appropriate MBC index in UAO, because it also reflects inspiratory besides expiratory flow rates, in contrast to MBCc [14][15][16][17]. The relationship between MBCm, MBCc, V 'Emax and exercise capacity is, however, not well established in UAO.…”
mentioning
confidence: 99%